2006
DOI: 10.1021/jp066437w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Molecule in the Small Dodecahedral Cage of a Clathrate Hydrate:  Quantum Five-Dimensional Calculations of the Coupled Translation−Rotation Eigenstates

Abstract: We report quantum five-dimensional (5D) calculations of the energy levels and wave functions of the hydrogen molecule, para-H2 and ortho-H2, confined inside the small dodecahedral (H2O)20 cage of the sII clathrate hydrate. All three translational and the two rotational degrees of freedom of H2 are included explicitly, as fully coupled, while the cage is treated as rigid. The 5D potential energy surface (PES) of the H2-cage system is pairwise additive, based on the high-quality ab initio 5D (rigid monomer) PES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(164 citation statements)
references
References 31 publications
10
151
2
Order By: Relevance
“…This uniquely high degree of realism and detail in simulating the INS spectra is not achievable by the approaches in the literature. It is made possible by our ability to compute accurately the fully coupled quantum 5D T-R energy levels and wave functions of the entrapped molecule on the 5D intermolecular PES 11,12,15,16 and, as shown here, use them as input for calculating the spectra.…”
mentioning
confidence: 99%
“…This uniquely high degree of realism and detail in simulating the INS spectra is not achievable by the approaches in the literature. It is made possible by our ability to compute accurately the fully coupled quantum 5D T-R energy levels and wave functions of the entrapped molecule on the 5D intermolecular PES 11,12,15,16 and, as shown here, use them as input for calculating the spectra.…”
mentioning
confidence: 99%
“…Bačić et al have studied these effects in much detail for hydrogen-containing clathrates [48][49][50][51][52][53][54], including explicit path-integral MD simulation [54]; based on these studies, it should be stressed that the classical MD results at 100 K and below reported in the present work needs to be interpreted with some caution due to the limitations of classical MD to describe accurately H 2 motion at low temperatures.…”
Section: Methodsologymentioning
confidence: 88%
“…Besides H 2 @C 60 , the theoretical study of which will be reported shortly, this includes molecular hydrogen in clathrate hydrates [19,29,30], metal-organic frameworks [31][32][33][34][35] and zeolites [36,37], among others. Finally, methodological extensions are in progress in our group to the INS spectra of nanoconfined polyatomic molecules such as methane [38] and water [39].…”
Section: Resultsmentioning
confidence: 99%
“…Our approach to the rigorous calculation of the coupled five-dimensional T-R energy levels and wave functions of a hydrogen molecule inside fullerenes, applied in this study to HD@C 60 , has evolved in our group over a number of years, in the course of the theoretical investigations of the quantum T-R dynamics of H 2 and its isotopologues entrapped in the cages of clathrate hydrates [19][20][21], fullerenes C 60 and C 70 [2,5], and an open-cage derivative of C 60 (ATOCF) [22]. A detailed description of the quantum five-dimensional methodology is available in [18], and therefore only the salient features are given here.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation